Social services in local social policy - Szluz, Beata (Polityka i Społeczeństwo, 2026)
The article illustrates local planning for the deinstitutionalisation of social services for the elderly, using the example of a municipality that was one of the first in Poland to adopt such a plan. Research confirms that the planning and implementation of services impacts residents’ quality of life. The aim of the analysis was to identify the resources and needs of the municipality’s residents (e.g. the elderly) and to develop a strategy for the deinstitutionalisation of social services. The findings demonstrate that diagnostic studies conducted in the municipality revealed specific needs among the elderly and individuals with disabilities, as well as families with children, including children with disabilities. Social services dedicated to people with mental disorders and those experiencing homelessness were also designed, although to a lesser extent due to lower demand. The local plan for the deinstitutionalisation of social services is considered pioneering at the national level.